Pediatric Skull Fracture Characteristics Associated with the Development of Leptomeningeal Cysts in Young Children after Trauma: A Single Institution's Experience. Issue 5 (May 2020) - Lopez, Joseph; Chen, Jennifer; Purvis, Taylor; Reategui, Alvaro; Khavanin, Nima; Iyer, Rajiv; Manson, Paul N.; Dorafshar, Amir H.; Cohen, Alan R.; Redett, Richard J.
Abstract : Background: Currently, the pathogenesis of leptomeningeal cysts, also known as growing skull fractures, is still debated. The purpose of this study was to examine the specific skull fracture characteristics that are associated with the development of growing skull fractures and describe the authors' institutional experience managing this rare entity. Methods: A retrospective cohort study was performed that included all patients younger than 5 years presenting to a single institution with skull fractures from 2003 to 2017. Patient demographics, cause of injury, skull fracture characteristics (e.g., amount of diastasis, linear versus comminuted fracture), concomitant neurologic injuries, and management outcomes were recorded. Potential factors contributing to the development of a growing skull fracture and neurologic injuries associated with growing skull fractures were evaluated using univariate logistic regression. Results: A total of 905 patients met the authors' inclusion criteria. Of these, six (0.66 percent) were diagnosed with a growing skull fracture. Growing skull fractures were more likely to be comminuted (83.3 percent versus 40.7 percent; p = 0.082) and to present with diastasis on imaging (100 percent versus 26.1 percent; p < 0.001; mean amount of diastasis, 7.1 mm versus 3.1 mm; p < 0.001). Univariate logistic regression analysis confirmed the role of a comminuted fracture pattern (OR, 7.572) and the degree of diastasis (OR, 2.081 per mm diastasis) as significant risk factors for the development of growing skull fractures. Conclusions: The authors' analysis revealed that fracture comminution and diastasis width are associated with the development of growing skull fractures. The authors recommend dural integrity assessment, close follow-up, and early management in young children who present with these skull fracture characteristics. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.